2014
DOI: 10.1002/eco.1569
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land use changes on hydrological components and macroinvertebrate distributions in the Poyang lake area

Abstract: Land use and land cover changes are important issues globally resulting in changing hydrological and ecological conditions. In addition to field sampling and measurements, we applied a model cascade comprising an ecohydrological model and a species distribution model. We developed five land use scenarios (three deforestation and two afforestation scenarios) for our Chinese study basin in the Poyang lake area. In detail, we assessed the impact of land use changes on the hydrologic regime and stream macroinverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 61 publications
1
22
0
1
Order By: Relevance
“…Projections were based on the 2006 land‐use map, in which existing forested areas below 600 m of elevation were converted into new land‐use categories: 50% of the forested area with a slope between 0 and 9% was converted into arable land, while the area with a slope between 9 and 19% was converted into 20% arable land and 15% tea plantations. This reduced forest cover from 70% to 53% (Schmalz et al ., ,b). These trends are comparable to published data (e.g.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Projections were based on the 2006 land‐use map, in which existing forested areas below 600 m of elevation were converted into new land‐use categories: 50% of the forested area with a slope between 0 and 9% was converted into arable land, while the area with a slope between 9 and 19% was converted into 20% arable land and 15% tea plantations. This reduced forest cover from 70% to 53% (Schmalz et al ., ,b). These trends are comparable to published data (e.g.…”
Section: Methodsmentioning
confidence: 97%
“…The hydrological time series in daily time steps from the Tankou gauging station (Jiangxi Hydrological Bureau, 2011, unpubl. data) was used to calibrate and validate the base model (Schmalz et al ., ). Four hydrological models were built for (i) the present projection reflecting current climate and land use, (ii) the climate‐change scenario with current land use but future climate conditions, (iii) the land‐use change scenario with current climate but future land‐use conditions and (iv) the combined scenario with future conditions for both climate and land use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maloney and Weller [84] found that past land use occurring 50 years ago still influences the present day conditions of streams. Similarly, Schmalz et al [41] also found negative effects of deforestation on the streams and aquatic ecosystems within a 30-year period.…”
Section: Land-use Changementioning
confidence: 86%
“…In general terms, the hydrological modeling procedure is similar as to that described for a different catchment in Schmalz et al (2014). Discharge for 51 subcatchment outlets at daily timesteps were extrapolated to the gridded stream network using flow accumulation (average R 2 = 0.89).…”
Section: Hydrologymentioning
confidence: 99%